Cloud Superstream. - Newman, Sam (O'Reilly Media, Inc., 2023)
Sponsored by F5 and Orca Security Many organizations today find themselves in a hybrid or multicloud environment, whether they planned it or just stumbled into it. But juggling workloads across these complex architectures is an incredibly tricky business. From isolated silos to costly resource sprawl, the challenges are immense. The supercloud has arrived on the scene to help, providing a layer of abstraction on top and offering a consistent way to manage it all. However, there's a lot of mystery still swirling around about what the supercloud is exactly and how it works. Join our expert speakers as they shed light on the different approaches to managing combined or multiple private, public, and edge clouds. They'll demystify common terms and concepts, help you gain a better understanding of what these various cloud models look like in practice, and show you how to successfully plan for, deploy, monitor, and secure these complex cloud architectures of the future. What you'll learn and how you can apply itUnderstand the various cloud deployment models and the opportunities and challenges of combining different types of cloud services and infrastructure Learn how to prepare for the complexities of hybrid or multicloud systems and identify the best solutions for your business or professional needs This recording of a live event is for you because... You're a developer, architect, engineer, or decision maker working with complex cloud environments. You want to be able to manage or leverage multiple cloud services and stay up-to-date on the latest developments in cloud technologies. Recommended follow-up: Read Cloud Without Compromise (book) Read Hybrid and Multicloud Management (report) Watch Infrastructure & Ops Hour: Multicloud with Gregor Hohpe (video) Take Multicloud Strategy Choices and Trade-Offs (live online training with Rashmi Tambe and Sunit Parekh) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.